ROBERT BURNS’S POEM “MY HEART’S IN THE HIGHLANDS” IN RUSSIAN TRANSLATION RECEPTION OF THE LAST QUARTER OF THE 19TH – THE FIRST HALF OF THE 20TH CENTURIES - Zhatkin, Dmitry; Ryabova, Anna (Revista Inclusiones, 2019)
The article considers the history of Russian translation reception of Robert Burns’s poem “My Heart’s in the Highlands” in the last quarter of the 19th – the first half of the 20th centuries. It is possible to find echoes of the perception of the well-known work of the Scottish author in I.S. Turgenev’s letters – to Pauline Viardot of November, 20 (October, 2) 1859 and November, 11 (November, 23) 1864, and to A.A. Fet of August, 16 (August, 28) 1871. At the same time, the first translation of the poem “My Heart’s in the Highlands”, created by M.N. Shelgunov, was issued only in 1879. Then the poem became popular: M.A. Rossiysky (1880, published in 1913), V.M. Mikheyev (the 1880-s), R.F. Brandt (O. Golovnin) (1886), V.E. Cheshikhin (Ch. Vetrinsky) (1890 or 1891), A.M. Fedorov (1896), O.N. Chyumina (1897), B.F. Lebedev (the 1930-s), D.S. Usov (1933), T.L. Shchepkina-Kupernik (published in 1936), M.A. Mendelssohn-Prokofyeva (1938), S.Ya. Marshak (1938) interpreted it. Some of these translations were published during lifetime of the authors, others were preserved in their personal archives, found and introduced by us (V.M. Mikheyev’s, V.E. Cheshikhin’s (Ch. Vetrinsky’s), B.F. Lebedev’s, M.A. Mendelssohn-Prokofyeva’s translations). In spite of allusions of Burns’s poem “My Heart’s in the Highlands” in Russian literature (for example, in N.M. Bogoras’s (Tan’s, V.G. Tan-Bogoraz’s) novel “Za okeanom” (“Over the Ocean”, 1904)) it had not been drawing attention of Russian literary critics for a long time; only after the publication of S.Ya. Marshak’s translation the researches, containing the analysis of the poem or accenting separate aspects related, were issued (E.I. Klimenko, S.A. Orlov, T.B. Liokumovich, A.A. Golikov). The publication of the brilliant translation of S.Ya. Marshak, who kept the atmosphere of the dialogue of the person and nature, motif of grief, caused by parting with native places, became a milestone in Russian translation reception of the poem “My Heart’s in the Highlands”; the best of new translations, which were published only at the end of the 20th century, were created with involuntary looking back at achievements of the translator-predecessor.